STUDI PRA-KELAYAKAN PENDIRIAN INDUSTRI SEDIAAN PEWARNA DAN PENGAROMA DAUN PANDAN DI KOTA TASIKMALAYA (Jurnal Teknologi Industri Pertanian, 2023)
Food coloring and flavoring from pandan leaves (Pandanus amaryllifolius) are natural dyes that can be used as an alternate to synthetic dyes. Meanwhile there is a potential to establish factory to support it as well as raw material availability. The purpose of this study was to conduct a pre-feasibility study of establishing a natural pandan preparations industry. The scope of this study includes market and marketing analysis, technical and technological analysis, management and organizational analysis, and financial analysis. The target market is the cake and bread industry, hotels, restaurants, and cafes in West Java. This industry is planned to be established in Tasikmalaya City, West Java with a production capacity around 44 ton/year. The results of the pre-feasibility study are that the industry is feasible with a Net Present Value of Rp 3.358.666.480; an Internal Rate of Return of 27.408%, a Net Benefit Cost Ratio 2.652; and 4.05 years payback period. Furthermore, based in the sensitivity analysis indicated that the decrease in selling price is more sensitive compared to the increase in operating costs and decrease in production capacity, and the increase in operating costs is more sensitive when compared to a decrease in production capacity. A decrease in selling price of 15% or an increase in operating costs of 20% has made the pandan preparation industry not feasible. Keywords: coloring, flavoring, pandan leave, pre-feasibility study